2009
DOI: 10.1080/02687030902777567
|View full text |Cite
|
Sign up to set email alerts
|

The use of the picture–word interference paradigm to examine naming abilities in aphasic individuals

Abstract: Background Although naming deficits are well documented in aphasia, on-line measures of naming processes have been little investigated. The use of on-line measures may offer further insight into the nature of aphasic naming deficits that would otherwise be difficult to interpret when using off-line measures. Aims The temporal activation of semantic and phonological processes was tracked in older normal control and aphasic individuals using a picture–word interference paradigm. The purpose of the study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 102 publications
4
32
0
Order By: Relevance
“…Previous studies have shown that tDCS can be proficiently employed to ameliorate language functions in aphasic patients (for reviews, see Cotelli et al, 2011;Hamilton et al, 2011a,b;Schlaug et al, 2011). Our findings add to this literature suggesting that tDCS can be selectively used to reduce SI in aphasic patients: in fact, although SI is a normally occurring phenomenon, its magnitude is usually heightened by brain damage to language areas (e.g., Hashimoto and Thompson, 2010;Thompson et al, 2012).…”
Section: Resultssupporting
confidence: 66%
“…Previous studies have shown that tDCS can be proficiently employed to ameliorate language functions in aphasic patients (for reviews, see Cotelli et al, 2011;Hamilton et al, 2011a,b;Schlaug et al, 2011). Our findings add to this literature suggesting that tDCS can be selectively used to reduce SI in aphasic patients: in fact, although SI is a normally occurring phenomenon, its magnitude is usually heightened by brain damage to language areas (e.g., Hashimoto and Thompson, 2010;Thompson et al, 2012).…”
Section: Resultssupporting
confidence: 66%
“…Only a few studies have used the picture-word interference paradigm for this purpose in neurologically impaired patients with naming deficits. In a study by Hashimoto and Thompson (2010), involving 11 individuals with mild aphasia resulting from stroke, aphasic participants showed abnormally heightened semantic interference effects at SOAs of −300 and 0 ms. But at SOA = +300, semantic interference effects disappeared as in normal age-matched speakers.…”
Section: Introductionmentioning
confidence: 99%
“…An important tool in studying spoken word production is the picture-word interference paradigm, which has been used to obtain evidence from healthy adult speakers (e.g., Damian & Martin, 1999;Schriefers, Meyer, & Levelt, 1990) and from impaired populations, including people with aphasia as a consequence of stroke (e.g., Hashimoto & Thompson, 2010) or neurodegenerative disease (e.g., Thompson et al, 2012). In this paradigm, speakers name pictures while trying to ignore spoken or written distractor words.…”
mentioning
confidence: 99%